From meta-system theory to the sustainable management of rivers in the Anthropocene - Cid, Núria; Erős, Tibor; Heino, Jani; Singer, Gabriel; Jähnig, Sonja C; Cañedo-Argüelles, Miguel; Bonada, Núria; Sarremejane, Romain; Mykrä, Heikki; Sandin, Leonard; Paloniemi, Riikka; Varumo, Liisa; et al. (Frontiers in ecology and the environment, 2022)
Regional-scale ecological processes, such as the spatial flows of material, energy, and organisms, are fundamental for maintaining biodiversity and ecosystem functioning in river networks. Yet these processes remain largely overlooked in most river management practices and underlying policies. Here, we propose adoption of a meta-system approach, where regional processes acting at different levels of ecological organization – populations, communities, and ecosystems – are integrated into conventional river conservation, restoration, and biomonitoring. We also describe a series of measurements and indicators that could be assimilated into the implementation of relevant biodiversity and environmental policies. Finally, we highlight the need for alternative management strategies that can guide practitioners toward applying recent advances in ecology to preserve and restore river ecosystems and the ecosystem services they provide, in the context of increasing alteration of river network connectivity worldwide.